A survey of real locomotion techniques for immersive virtual reality applications on head-mounted displays - Cardoso, Jorge C. S. (2019)
Locomotion is a fundamental activity in Virtual Reality (VR) and has been the focus of a large body of research since the implementation of the first systems. In real locomotion techniques, users physically move in the real world to affect movement in the Virtual Environment (VE). Real locomotion has been found to perform better than other forms of locomotion for many tasks. To overcome the challenges imposed by restricted physical space, researchers have devised ingenious interaction techniques for real locomotion. In this paper, we present a survey of interaction techniques for real locomotion in VR. Our analysis is focused on the interaction techniques – the combination of devices, user’s actions, and system’s responses. We categorize interaction techniques for real locomotion in VR into: unmediated, warnings, reorientation/resetting, scaling, redirection, and dynamic VE. These categories represent fundamentally different approaches to real locomotion and user action feedback. We further characterize techniques in each of these categories according to category-specific parameters. Finally, it is important to state that this paper was developed with the aim of helping newcomers to the field to understand and implement the techniques here presented.